Efficiency of Using Biomass from Energy Crops for Sustainable Bioenergy Development - KULYK, Maksym; KALYNYCHENKO, Oleksandrr; PRYSHLIAK, Natalia; PRYSHLIAK, Viktor (Journal of Environmental Management and Tourism; Vol 11 No 5 (2020): JEMT Volume XI Issue 5(45) Fall 2020DO - 10.14505//jemt.v11.5(45).02, 2020)
The need to study energy crops as an alternative source of energy for providing the population and rural development is justified in the article. In the course of the study, the following methods were used: laboratory – to determine the moisture content in the phytomass, field – to determine the quantitative indicators of plants and biomass productivity, special – to determine the energy and economic efficiency of biomass production. Features of yield formation and yield of dry biomass of energy crops by quantitative indices of plants were determined. The economic and energy efficiency of biomass production, as well as the output of solid biofuel, its energy intensity and energy output have been calculated. A logistic scheme for biomass cultivation including the use and supply of biomass from biomass energy crops (from producer to consumer) has been developed. It has been found that switchgrass and giant miscanthus of the third to fifth year of vegetation form a high yield of dry biomass (up to 15.2 and 18.8 t / ha, respectively) with a maximum level of production profitability - up to 108.6% and 128.1%, provide high indicators of biofuel output (up to 18.2 and 24.0 t / ha) and energy (up to 313.0 and 396.0 GJ / ha) with an average level of energy efficiency coefficient (Kee> 4.5).